2022
DOI: 10.3390/rs14236067
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Historical Land Use and Urban Flood Simulation in Xi’an, Shannxi, China

Abstract: Reconstruction of historical land uses helps to understand patterns, drivers, and impacts of land-use change, and is essential for finding solutions to land-use sustainability. In order to analyze the relationship between land-use change and urban flooding, this study used the Classification and Regression Tree (CART) method to extract modern (2017) land-use data based on remote sensing images. Then, the Paleo-Land-Use Reconstruction (PLUR) program was used to reconstruct the land-use maps of Xi’an during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Previous studies in semiarid areas showed that rainfall had a more significant driving effect on NDVI than temperature, further supporting the view of the "short board effect." The enormous pressure of continuous population growth, the intensification of human socioeconomic activities, the development of the planting industry, and the expansion of agricultural areas in the research area has inevitably led to a continuous reduction in forest vegetation [54,55], causing damage to the environment [56]. Human activity factors had a negative impact on the direct pathway affecting the NDVI, and the impact was gradually strengthening.…”
Section: Main Control Factors Of Vegetation Indexmentioning
confidence: 99%
“…Previous studies in semiarid areas showed that rainfall had a more significant driving effect on NDVI than temperature, further supporting the view of the "short board effect." The enormous pressure of continuous population growth, the intensification of human socioeconomic activities, the development of the planting industry, and the expansion of agricultural areas in the research area has inevitably led to a continuous reduction in forest vegetation [54,55], causing damage to the environment [56]. Human activity factors had a negative impact on the direct pathway affecting the NDVI, and the impact was gradually strengthening.…”
Section: Main Control Factors Of Vegetation Indexmentioning
confidence: 99%
“…On the other hand, with the development of computer science, many software and numerical models have been presented for flood modeling. Among software models, HEC‐RAS (Ghimire et al, 2022; Namara et al, 2022; Sejati et al, 2022), HEC‐HMS (Altaf & Romshoo, 2022; Nadeem et al, 2022; Shah & Lone, 2022), MIKEs (Mike11, Mike21, Mike Flood, Mike Urban) (Dikici et al, 2022; Goumas et al, 2022; Li et al, 2022; Zhang et al, 2022; Zhou, Teng, et al, 2022; Zhou, Zheng, et al, 2022), Bentley Open Flow (de Andrade et al, 2022; Ellwood et al, 2022; Khakhar et al, 2022), Flo‐2D (Gerundo et al, 2022; Komolafe, 2022; Liu et al, 2022; Wang, Luo, et al, 2022), and CCHE (Lee et al, 2020; Kakati et al, 2022; Poorzaman et al, 2022) models can be mentioned. Also, the most applied numerical models include artificial neural network (Ahmad et al, 2022; Dahri et al, 2022; Wang, Yang, et al, 2022), random forest (Abedi et al, 2022; El‐Magd & Ahmed, 2022; Ha & Kang, 2022; Zhu & Zhang, 2022), and analytic hierarchy process (Bouamrane et al, 2022; Roy et al, 2023; Souissi et al, 2022; Vilasan & Kapse, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…With global warming and urbanization, the frequency of extreme natural disasters has increased, posing challenges to regional ecological security [1][2][3]. Issues such as biodiversity reduction [4,5], habitat loss [6], and eutrophication [7,8] have become prominent, thereby hindering balanced development and emphasizing the importance of planning, protecting, and governing regional ecological security patterns (ESPs) [9][10][11]. As a vital ecological barrier in China, the Qinling Mountains region plays a crucial role in protecting the environment and establishing rational ESPs [12,13].…”
Section: Introductionmentioning
confidence: 99%